Uma leitura do I Livro de Tombo do Convento do Carmo em Salvador: contribuição à construção histórica da Ordem dos Carmelitas na Bahia-colonial - Beatriz Junqueira Pedras (2000)
It presents a study of the Livro Iº de Tombo(First Book Archives) from the Carmel Convent of Salvador, the oldest registry of documents among the records of the Carmelite Orden in Brazil. This Book contains manuscript documents such as: crown land donations in the colony, deeds, receipts, proxies, royal orders, wills, crown land leases, rentals, escritos de liberdade (freeing of slaves), documents referring to religious associations and unclassifiable documents. These documents compose frame and context of the socio-cultural, historical and religious characteristics at that period. After the study of subjects taken as important for theoretical foundation of the research, such as Padroado (ecclesiastical patronage), Carmelite mission in Brazil and archives technical concepts, the Livro Iº Tombo(First Book Archives) is analyzed in the physical and content aspects. The reading of the Livro Iº Tombo (First Book Archives) is done in a historical perspective of the cultural and religious development in the formative process of the nation, during the three centuries covered by the dates of the Book documents (XVI, XVII and XVIII centuries). The aim is to bring to the public the largest possible quantity of information as a contribution of the Archives and the Carmelite Order to Information Science. This is done through the study of the characteristics of these ancient manuscripts like cetras (flourishes on old manuscripts) and water marks or through the study of the form of text with archaic language and terms that motivated the preparation of a glossary, for better understanding of the meanings. The elements for the historical meaning that constitute a valuable source of information, deserved the elaboration of a search instrument in the form of onomastic index of all the quoted names.